Echinoderm research perspectives: A Central American bibliometric review - Alvarado Barrientos, Juan José (2021)
Introduction: Central America, a narrow strip of land dividing the Atlantic and Pacific oceans, has a high diversity of marine and terrestrial species. Echinoderms are one of the most diverse marine groups with 420 reported species. Objective: To summarize echinoderm research in Central America. Methods: We compiled the literature from SCOPUS, Web of Science, SciELO, Google Scholar, Biodiversity Heritage Library, the Internet Archive and the Smithsonian Library. Results: We found 324 publications dating from 1840 to 2020; the early studies had a strong taxonomic focus, but after the 1970s, ecology, evolution and reproduction gained prominence. Echinoidea is the most studied class (38% of publications) due to its use in evolutionary studies as well as the importance of the genus Diadema in reef ecology and dynamics. Conclusion: We recommend more research on fisheries management, conservation and environmental education; and greater integration of local and international research.